2021
DOI: 10.1155/2021/6650045
|View full text |Cite
|
Sign up to set email alerts
|

F1012‐2 Induced ROS‐Mediated DNA Damage Response through Activation of MAPK Pathway in Triple‐Negative Breast Cancer

Abstract: We have previously reported that F1012-2, a sesquiterpene lactone isolated from the Chinese herbal medicine Eupatorium lindleyanum DC., exhibits strong effects against Triple Negative Breast Cancer (TNBC). In this study, we found F1012-2 effectively inhibited cell migration and invasion detected by wound healing and transwell assays. In order to elucidate the potential mechanisms of F1012-2, we further studied its effect on DNA damage in TNBC cell lines. Using single cell gel electrophoresis (comet assay), imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Together with DNA damage, response factors including tumor suppressor p53 and NF-κB become activated [24]. We previously reported that F1012-2 induced DNA damage in TNBC [14]. In the present study, F1012-2 not only regulated the expression of p53, but also significantly decreased the expression levels of NF-κB family members p-p65 and p105 and had no effect on the expression of p65 and p50.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Together with DNA damage, response factors including tumor suppressor p53 and NF-κB become activated [24]. We previously reported that F1012-2 induced DNA damage in TNBC [14]. In the present study, F1012-2 not only regulated the expression of p53, but also significantly decreased the expression levels of NF-κB family members p-p65 and p105 and had no effect on the expression of p65 and p50.…”
Section: Discussionsupporting
confidence: 46%
“…Western blotting was carried out as described previously [14,16]. Cells were seeded on 6-well culture dishes (8×10 5 cells/dish) and treated with the indicated concentrations of F1012-2 for 24 h. Cells were harvested, washed twice with ice-cold PBS, lysed by incubation in RIPA buffer for 30 min on ice, and then centrifuged at 16100 ×g at 4°C for 15 min.…”
Section: Western Blotting Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, it is reported that the elevated ROS can inhibit Bcl-2 expression and activate Bax expression in the mitochondria [ 42 ]. F1012-2, another compound isolated from Eupatorium lindleyanum DC., has been reported to cause DNA damage in TNBC cells by increasing ROS production [ 43 ]. In this study, the generation of ROS was notably elevated in TNBC cells upon exposure to EO.…”
Section: Discussionmentioning
confidence: 99%
“…HER2+ breast cancer usually grows aggressively, and HER2-targeted antibody therapy using pertuzumab/trastuzumab plus a taxane has been widely used as the first-line standard therapy in HER2-enriched BC patients [5]. TNBC accounts for 15-20% of all breast cancers; it is considered to be one of the most drug-resistant cancer types and is characterized by a high malignancy [6]. Due to the absence of molecular targets, no desirable targeted therapeutic agents have been clinically approved for TNBC, so the mortality rate remains high [7,8].…”
Section: Introductionmentioning
confidence: 99%